Ivabradine improves survival and attenuates cardiac remodeling in isoproterenol-induced myocardial injury - Simko, Fedor; Baka, Tomas; Repova, Kristina; Aziriova, Silvia; Krajcirovicova, Kristina; Paulis, Ludovit; Adamcova, Michaela (Fundamental & clinical pharmacology, 2021)
This study investigated whether ivabradine, a selective If current inhibitor reducing heart rate (HR), is able to improve survival and prevent left ventricular (LV) remodeling in isoproterenol-induced heart damage. Wistar rats were treated for 6 weeks: controls (n = 10), ivabradine (10 mg/kg/day orally; n = 10), isoproterenol (5 mg/kg/day intraperitoneally; n = 40), and isoproterenol plus ivabradine (n = 40). Isoproterenol increased mortality, induced hypertrophy of both ventricles and LV fibrotic rebuilding, and reduced systolic blood pressure (SBP). Ivabradine significantly increased survival rate (by 120%) and prolonged average survival time (by 20%). Furthermore, ivabradine reduced LV weight and hydroxyproline content in soluble and insoluble collagen fraction, reduced HR and attenuated SBP decline. We conclude that ivabradine improved survival in isoproterenol-damaged hearts.
Keywords: modely nemocí na zvířatech; zvířata; Rats; Disease Models, Animal; funkce levé komory srdeční; mužské pohlaví; isoprenalin; Cardiotonic Agents; ivabradin; Ventricular Remodeling; Rats, Wistar; Isoproterenol; Myocardial Infarction; srdeční selhání; krysa rodu Rattus; potkani Wistar; remodelace komor; Animals; infarkt myokardu; Ivabradine; Heart Failure; Ventricular Function, Left; Male; kardiotonika